Ekonomia neoklasyczna versus ekonomia behawioralna. Libertariański paternalizm a reforma emerytalna - Ostapiuk, Aleksander (Annales. Etyka w Życiu Gospodarczym, 2019)
The goal of the article is to criticise neoclassical economics from the behavioural economics perspective on the example of Poland’s reform of the retirement system (the possibility of earlier retirement). The creators of the reform assume that people are rational and will choose the best option and save enough for retirement. Thanks to conclusions from psychology we know that people cannot discount utility in time, but they behave in accordance with hyperbolic discounting. This situation leads to the conflict between preferences in time. To resolve this conflict, the concept of multiple selves is presented. Different preferences in time are not the problem for neoclassical economics, which assumes that people choose what is best for them (revealed preferences). The criticism of this assumption is presented along with the limitations of perceiving rationality in the instrumental sense. Thanks to axiomatic assumptions, neoclassical economists could dismiss conclusions from behavioural economics which concerns human irrationality. It proves that people do not always make the best choices, which is observable on the example of people who take early retirement. The concept of libertarian paternalism is presented as a way of helping people to make the “right” choices. The possibility of early retirement is presented as the default option. The author comes to the conclusion that this state is a flawed choice architecture because, despite its negative consequences, many people will choose early retirement.